Multiferroic Materials: A Room‐Temperature Ferroelectric Ferromagnet in a 1D Tetrahedral Chain Network (Adv. Mater. 24/2019). Issue 24 (7th June 2019) - Kang, Kyeong Tae; Roh, Chang Jae; Lim, Jinyoung; Min, Taewon; Lee, Jun Han; Lee, Kyoungjun; Lee, Tae Yoon; Kang, Seunghun; Seol, Daehee; Kim, Jiwoong; Ohta, Hiromichi; Khare, Amit; et al.
Abstract : A one‐dimensional tetrahedral chain network in a brownmillerite structure gives rise to a coupled ferroelectric and ferromagnetic behavior. In article number1808104, Woo Seok Choi and co‐workers describe the discovery of a room‐temperature ferroelectric ferromagnet in a SrFeO2.5 epitaxial thin film, which exhibits an unconventional combined polar distortion with the mechanism of the coupled ferro‐orderings.